A GENDER PERFORMATIVITY ANALYSIS ON GENDER NORMS PORTRAYED IN LOUISA MAY ALCOTT’S LITTLE WOMEN - Traesar, Livia; Sujiwa, Krisna (Universitas Respati Yogyakarta (UNRIYO), 2025)
This research analyses gender norms and performativity in Louisa May Alcott's Little Women (1868) using Judith Butler's gender performativity theory. Alcott's semi-autobiographical portrayal of the March sisters paints a vivid picture of nineteenth-century American gender norms and their societal ramifications. This study focuses on Jo March and Theodore